2019
DOI: 10.1111/btp.12636
|View full text |Cite
|
Sign up to set email alerts
|

Geographic space, relief, and soils predict plant community patterns of Asteraceae in rupestrian grasslands, Brazil

Abstract: We investigated the effects of geographic distance and environmental heterogeneity on Asteraceae communities in the rupestrian grasslands of the Espinhaço Range, southeastern Brazil. Asteraceae species composition and relative abundance were sampled in 21–1 ha plots distributed across park conservation units, comprising an environmental gradient in soils and relief (elevation and slope). We found high levels of heterogeneity overall in assemblages of herbaceous and woody Asteraceae species at the intermediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…Closer investigation of the endangered species that were not collected showed that two of them are common either in the northern "Bahia" CdoE or in the more westerly Serra Geral de Goia´s. For species where wide-scale distributional data could not explain absence, microdistributional differences or microhabitat specialization, as proposed by Chaves et al (2019), stochastic distribution, or a combination of these are the most likely explanations. Percentages of gravel, sand, and silt in the soil explained 67% of the difference between mycorrhizal communities (Carvalho et al, 2012).…”
Section: Endangered Species and Conservation Statusmentioning
confidence: 97%
See 4 more Smart Citations
“…Closer investigation of the endangered species that were not collected showed that two of them are common either in the northern "Bahia" CdoE or in the more westerly Serra Geral de Goia´s. For species where wide-scale distributional data could not explain absence, microdistributional differences or microhabitat specialization, as proposed by Chaves et al (2019), stochastic distribution, or a combination of these are the most likely explanations. Percentages of gravel, sand, and silt in the soil explained 67% of the difference between mycorrhizal communities (Carvalho et al, 2012).…”
Section: Endangered Species and Conservation Statusmentioning
confidence: 97%
“…both parks, and in many cases, frequency data have been obtained from RAPELD modules (see Chaves et al, 2019). Five such endangered species have been recorded from protected areas for the first time (species marked with b in Table 2).…”
Section: Endangered Species and Conservation Statusmentioning
confidence: 99%
See 3 more Smart Citations